2023
DOI: 10.1021/acs.inorgchem.3c00486
|View full text |Cite
|
Sign up to set email alerts
|

Organic Hybrid Antimoniotungstate Layered Ionic Crystal: Synthesis, Structure, and Interlayer-Confined Proton Conduction

Abstract: A synchronous crystal- and microstructure-dependent strategy was implemented to synthesize the organic hybrid antimoniotungstate layered ionic crystal Na5.5H6.5[(SbW9O33)2{WO2(OH)}2{WO2}­RuC7H3NO4]·36H2O, and the layered structure was constructed through the Na+ bridged sheet and the hydrogen-bonded layers. It displayed an effective proton conductivity of 2.97 × 10–2 S cm–1 at 348 K and 75% RH, owing to the complete interlayer confined hydrogen-bond network formed by the hydrogens of interlayer crystal waters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As shown in Figure b, as the temperature rose from 30 to 75 °C under 80% RH, the conductivity increased continuously to 3.07 × 10 –2 S cm –1 , which was attributed to the acceleration of proton transfer with the temperature rising up (Figure b) . Although ordinary in comparison with the proton-conducting materials such as MOF, COF, HOF, etc., it is superior to typical proton-conducting materials in POMs , (Table S7). At last, the activation energy ( E a ) was evaluated by the Arrhenius equation [σ T = σ 0 exp(− E a / k b T )], and calculations showed that E a at 80% RH was estimated to be 0.22 eV (Figure d), indicating that the Grotthuss mechanism is dominant during the process of proton conduction, given that E a is in the range from 0.1 to 0.4 eV .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure b, as the temperature rose from 30 to 75 °C under 80% RH, the conductivity increased continuously to 3.07 × 10 –2 S cm –1 , which was attributed to the acceleration of proton transfer with the temperature rising up (Figure b) . Although ordinary in comparison with the proton-conducting materials such as MOF, COF, HOF, etc., it is superior to typical proton-conducting materials in POMs , (Table S7). At last, the activation energy ( E a ) was evaluated by the Arrhenius equation [σ T = σ 0 exp(− E a / k b T )], and calculations showed that E a at 80% RH was estimated to be 0.22 eV (Figure d), indicating that the Grotthuss mechanism is dominant during the process of proton conduction, given that E a is in the range from 0.1 to 0.4 eV .…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, the conductivity of 1 -dehyd is 40-fold that of compound 1 at 55% RH. This result concludes that the large number of water molecules within complex 1 is beneficial for promoting the proton conduction process . The infrared spectra of the initial compound 1 and its dehydrated form, 1 -dehyd, were examined before and after proton conduction testing (Figure S6).…”
mentioning
confidence: 84%
“…In addition, most of the related studies focused on POMs built from 3d block transition metals and lanthanide elements, while rare studies were conducted on 4d block transition metal-based POMs in this field. For example, organo-ruthenium supported antimoniotungstate [Sb 2 W 20 O 70 (RuC 10 H 14 ) 2 ] 10– was attained in 2009; bis­[tetraruthenium­(IV)]-containing polyoxometalates of [{Ru IV 4 O 6 (H 2 O) 9 } 2 Sb 2 W 20 O 68 (OH) 2 ] 4– was reported in 2012, and Niu group reported an organic hybrid antimoniotungstate layered ionic crystal Na 5.5 H 6.5 [(SbW 9 O 33 ) 2 {WO 2 (OH)} 2 {WO 2 }­RuC 7 H 3 NO 4 ]·36H 2 O with high proton conductivity in 2023 …”
mentioning
confidence: 99%
“…36 Besides, our group reported a high-conductivity POM Na 5.5 H 6.5 [(SbW 9 O 33 ) 2 {WO 2 (OH)} 2 {WO 2 }RuC 7 H 3 N O 4 ]·36H 2 O with σ = 2.97 × 10 −2 S cm −1 (75% RH, 348 K) in 2023. 37 Compared with these POM-based proton conductive materials (Table S3, ESI‡), ZrSPs as proton conduction materials are rare, and the proton conductivity of 1 is superior to that of most POM-based proton conductive materials.…”
mentioning
confidence: 99%